Development of ARM+FGPA-based controller for power conversion applications - Toh, Vernice Li Li (2019)
Aerospace and marine power converters require universal digital controllers with sufficient peripherals to cover a broad range of topologies. The integration of a fast processor core within a Field Programmable Gate Array (FPGA) shows great potential in providing a high level of flexibility without compromising the controller size and the number of components. The project involves the design of PID Controller for mixed digital and analog domains (ARM + FPGA design). This project was done in collaboration with Rolls-Royce Singapore Pte Ltd. The program was developed for the Cyclone V SoC, which is an FPGA combined with a dual-core ARM Cortex-A9 Hard Processor System (HPS) and some peripherals. The project aims to explore the best means of the implementation of a PID Controller in the Cyclone V SoC. It was found that the assignment of the controller’s workings to ARM and the data acquisition and controller PWM output to FPGA was the most effective and flexible method for the implementation of a PID controller. Through this method, the PID controller could be optimised to have an update rate of 645 kHz. This project addresses current design and prototype testing challenges and pushes controller design boundaries, so as to enable the successful development of controllers for the next generation of power converters.